Robust task-space motion control of a mobile manipulator using a nonlinear control with an uncertainty estimator. (April 2018) - Mishra, S.; Londhe, P.S.; Mohan, S.; Vishvakarma, S.K.; Patre, B.M.
Highlights: Robust task-space tracking control of mobile manipulator is proposed. The effect of lumped disturbance is compensated by an effective and efficient disturbance estimator. Efficacy of the proposed controller has been demonstrated on 7-dof mobile manipulator. The proposed scheme shows better immunity to external disturbances and parameter uncertainties. The robustness of the proposed controller is evaluated over existing controllers. Graphical abstract: Abstract: In this study, a robust nonlinear control method with an uncertainty estimator is proposed and applied to a kinematically redundant mobile manipulator (MM) position tracking in its task space. The proposed MM has four degrees-of-freedom (dof) serial manipulator mounted on three of mobile bases. The proposed method incorporates a feed-forward control term to reinforce the control action with extravagance from the desired acceleration vector; a disturbance estimator to reimburse for the unknown effects such as parametric uncertainties, external disturbances, unmodeled dynamics and a decentralized PID (proportional-integral-derivative) controller as a feedback loop to strengthen the stability of the system. The main strengths of the proposed scheme are its high robustness against parameter uncertainties and external disturbances, simplicity in design and ease of implementation. The effectiveness, feasibility, and robustness of the proposed method are illustrated using computer-based simulations with and without uncertainty estimator.